P14.57 WHO grade II and III meningioma: a large mono-institutional retrospective series. (9th September 2021) - Simonetti, G; Gaviani, P; Farinotti, M; Legnani, F; Pollo, B; Pinzi, V; Botturi, A; Redaelli, V; Silvani, A
Abstract: BACKGROUND: Meningiomas are usually considered benign lesions, however a part of them can show very aggressive behavior with tendency to metastasize. This subgroup is known as high-grade meningiomas (HGM). Due to the rarity of the disease, effective medical treatments are lacking, especially at the time of recurrence. We aim to describe the clinical, radiological and molecular features of a large population of HGM diagnosed between 2010 and 2018. The secondary aim was to evaluate survival (PFS) and overall survival (OS). MATERIAL AND METHODS: We collected clinical and survival data from primitive WHO grade II and III meningioma patients treated at Fondazione IRCCS Istituto Neurologico Carlo Besta from January 2010 to December 2018. Records were collected on a web-based platform (Microsoft Excel) that was customized for this study. The database, contained epidemiological, diagnostic (radiological and histological/molecular), surgical, therapeutic and recurrence information, as well as survival data. RESULTS: 183 patients (105 females and 78 males), with median age of 58 years (25–88), were included; 168 were atypical, 12 anaplastic, 3 rhabdoid. Overall, m-PFS was 4.2 years, and m-OS was 10.3 years. Gross-total resection had a 5-year survival rate of 95% compared with subtotal/partial resection (86% and 67%) (p=0.002). Higher expression of Ki-67/MIB-1 seems associated with higher risk of death (HR:1.06 with 95% CI, 1.00–1.12, p=0.03). No statistically significant differences were seen in survival between the group managed with a wait-and-see strategy vs the group treated with RT/SRS while a difference on PFS was seen (4.1 years vs 5.2 years p=0.03). After second recurrence, the most employed treatments were systemic therapies with a very limited effect on disease control. CONCLUSION: Data confirmed the aggressive behavior of HGM. The extent of resection seems to correlate with a favorable outcome regardless histological subtypes. The role of RT/SRS remains controversial, with no statistically significant impact on OS but a possible role on PFS. At relapse, no chemotherapies are able to achieve disease control and recurrent HGM remains the real challenge for future research, focusing on biological/molecular predictors in order to achieve a patient-tailored treatment.This retrospective study allowed to analyzed the largest national recent series of aggressive meningiomas with the purpose of identify relevant outcome measures for future prospective studies. Our findings could be important to give a snapshot of the current attitude to treat aggressive meningiomas but also to inspire national and international collaboration in order to provide evidence-based management strategies trying to obtain a standard of care.